City and non-city. The ’ecotonal’ dimension of peri-urban landscapes - Protasoni, Sara (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
The article discusses the concept of peri-urban landscape, emphasising its ecotonal dimension, as a boundary placed between differently identified spatial/environmental units. A boundary that is extended to include multiple, mutable and multi-scale systems of relationships that engage spatial, ecological, cultural and social elements. This reinterpretation of the idea of the ‘peri-urban’ is explained with reference to the new relevance of the ecological approach and to the profound transformation of the idea of nature that is taking place in architectural reflection and public debate in general. The ‘city-archipelago’ and the ‘porous city’ are proposed as two of the most relevant images driving the transition towards new approaches to the design of parks, urban forests and urban campaigns, where new forms of public/collective space are now being tested through the reinterpretation of the notion of leisure, training and bewilderment.